2020
DOI: 10.1063/1.5133855
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamic simulation of tool groove wear in nanoscale cutting of silicon

Abstract: Tool wear is one of the bottlenecks that decrease the machinability of hard and brittle materials in single point diamond turning (SPDT). Specifically, a microgroove generated on the cutting edge is an important character of tool wear, which leads to the formation of subcutting edges and facilitates the ductile to brittle transition in machining. However, the mechanism of the groove wear influence on the machined workpiece, especially the subsurface damage, is not clear just by the experimental investigations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…In their study a correlation between the stagnation zone shape and the tool cutting edge radius was described. Liu et al [28] have observed subsurface damage during the CMDS of the silicon cutting mechanism. However, the subsurface damage was detected as non-identifiable structures in the silicon crystal and were parallel to the shear plane.…”
Section: Resultsmentioning
confidence: 99%
“…In their study a correlation between the stagnation zone shape and the tool cutting edge radius was described. Liu et al [28] have observed subsurface damage during the CMDS of the silicon cutting mechanism. However, the subsurface damage was detected as non-identifiable structures in the silicon crystal and were parallel to the shear plane.…”
Section: Resultsmentioning
confidence: 99%
“…MD studies reveal the thermo-chemical mechanism is due to the reduction in the cohesion energy of carbon under the high cutting temperature [13], as well as the graphitization of diamond lattice [125]. The formation of SiC hard particle from the dangling bonds at the tool flank face is considered as another source of abrasive wear during the nanometric cutting of Si [179], and the induced groove on flank face increases the subsurface damaged region and promotes the formation of polycrystalline structure [180]. Similar wear patterns are also observed in the machining of SiC (Figure 13d), while the cutting length the tool edge can sustain is only tens of metres due to the great hardness of the workpiece [181].…”
Section: Tool Wear Mechanismmentioning
confidence: 99%
“…[17][18][19][20] On the premise of an accurate modeling, the results will show good agreement with that by experimental method according to the reasonable potential function selection. As an example, Liu et al [21] conducted MD simulations to explore the effect of groove wear on the subsurface damage of monocrystalline silicon during the diamond cutting process, and the expansion of the groove was also studied by considering the temperature and stress distribution on the tool edge. Mylvaganam et al [22] applied MD method to research the scratch-induced deformation in monocrystalline silicon; they found that the dominant mechanisms are amorphous phase transformation and nano-twins.…”
Section: Introductionmentioning
confidence: 99%